Interfacial engineering of heterostructured Fe-Ni3S2/Ni(OH)2 nanosheets with tailored d-band center for enhanced oxygen evolution catalysis. Issue 45 (3rd November 2022) - Li, Gao; Ma, Zhanfeng; Li, Weirong; Nie, Yuhang; Pei, Lang; Zhong, Jiasong; Miao, Qian; Hu, Mao-Lin; Wen, Xin
Abstract : The OER catalytic activities of Fe-Ni3 S2 nanosheets can be well manipulated by tailoring the d band center positions via interfacial engineering strategy. Abstract : Hydrogen production by electrochemical water splitting suffers from high kinetic barriers in the anodic oxygen evolution reaction (OER), which limits the overall efficiency. Herein, we report a structural and electronic engineering strategy by integrating self-standing Fe-doped Ni3 S2 (denoted by Fe-Ni3 S2 ) nanosheet arrays with Ni(OH)2 subunits to form heterostructured Fe-Ni3 S2 /Ni(OH)2 on a Ni Foam substrate. The strong electronic interaction between the Fe-Ni3 S2 and Ni(OH)2 constituents contributes abundant catalytic sites and ensures high electron transfer. Moreover, the combined experimental and theoretical study revealed that the coupling of Ni(OH)2 onto the Fe-Ni3 S2 is favorable for lowering the activation energy of water oxidation for favorable OER kinetics and upshifting the Ni d-band center to facilitate the adsorption of O-containing intermediates. Consequently, the optimized Fe-Ni3 S2 /Ni(OH)2 hybrid catalyst exhibits excellent OER performance in alkaline electrolytes with an ultralow overpotential of 202 mV at 10 mA cm −2, a small Tafel slope of 50.6 mV dec −1, and long-term durability under high current density (0.25 A cm −2 ) for up to 60 h without significant deactivation. Moreover, a two-electrode Fe-Ni3 S2 /Ni(OH)2 ||Pt/C electrolyzer requires only a low voltage of 1.54 V at 10 mA cm −2 for overall water splitting. This study emphasizes the importance of interface and surface engineering in achieving highly efficient electrocatalysts.